The Algorithmic Edge: Does Artificial Intelligence Truly Enhance Health Screening Accuracy? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI in health screening represents one of the most transformative shifts in modern medicine. Health screening, the ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning